Psychiatric Morbidity And Quality Of Life In Patients With Hemodialysis And Continuous Ambulatory Peritoneal Dialysis (Annals of Medical Research, 2021)
None
Keywords: Hemodialysis Continue Ambulatory Peritoneal Dialysis (CAPD), Psychiatric morbidity, Quality of life